Patient and primary care perspectives on hypertension management: short report of a qualitative study in a tribal health system. Issue 1 (31st December 2022) - Schaefer, Krista R.; Todd, Michael R.; Trinidad, Susan Brown; Robinson, Renee F.; Dillard, Denise A.
ABSTRACT: The prevalence of self-reported hypertension is higher among Alaska Native and American Indian (ANAI) individuals than in the majority USA population. Although hypertension is the primary modifiable risk factor for cardiovascular disease and stroke, it can be difficult to manage successfully. The objective of this study was to explore patients' and providers' perspectives about hypertension, hypertension management strategies, and patient-provider communication strategies within a tribally-owned and operated health system in Alaska. We conducted four focus groups that included 16 ANAI patients and five primary care providers. Patient participants tended to consider hypertension a transient state, in contrast with providers' understanding of hypertension as a chronic condition. Differences were noted in participants' perceptions regarding providers' counselling and education efforts, with providers feeling that current strategies are effective and patients desiring a more personalised discussion about hypertension. Patients expressed preferences for behaviour change approaches compared with pharmacotherapy; providers often resorted to medication as a first step towards controlling blood pressure. Our findings suggest areas of potentially promising future research with respect to patient-provider communication and treatment of hypertension.